Role of Strategic Leadership in Applying Total Quality Management: A Field Study in Private Hospitals in the Capital, Sana'a - Mohyaldeen, Ali Mohssen Ali; Alamri, Abdu Ahmed Ali (Zenodo)
Total quality management has gained extensive prominence over the last few decades and continues to play a significant role in modern healthcare delivery. This study aimed to measure the role of strategic leadership in applying TQM in private hospitals in the capital Sana'a. Cross-sectional study was adopted. The research sample included (230) employees in senior administrative positions at six hospitals. To achieve the aim of the research, a questionnaire was used to collect data related to the research variables. The data was analyzed using statistical software (SPSS) to obtain the results. The current study found a positive correlation and role between the practice of strategic leadership in the application of total quality management, and it was found that there is a varying positive role for the dimensions of strategic leadership in the application of total quality management, there was the most role the strategic orientation and the least role is the human capital development. The current study contributes to the literature by showing the concepts and dimensions of strategic leadership and total quality management. This study is also the first to analyze the role of strategic leadership in the application of total quality management in the health sector in Yemen. The study shows the important role of strategic leadership in the application of total quality management, which is reflected in the success and development of private hospitals.
Keywords: Strategic Leadership; Strategic Direction; Total Quality Management; Private Hospitals